Secondary traumatic stress among victim advocates: prevalence and correlates. Issue 5 (3rd September 2018) - Benuto, Lorraine T.; Newlands, Rory; Ruork, Allison; Hooft, Sierra; Ahrendt, Andrew
ABSTRACT: Purpose : The purpose of this study was to establish the prevalence of Secondary Traumatic Stress (STS) among victim advocates and to determine if risk factors (for the development of STS) that have been cited in the literature (with other populations) are applicable to victim advocates. Methods : Data was collected from 135 victim advocates using an online survey. Results : The prevalence rate of STS among victim advocates is approximately 50% and risk factors include number of hours worked per week, direct service hours, and working with adult survivors of child sexual abuse. Discussion : Our results suggest that cumulative trauma exposure acts as risk factors to the development of STS among victim advocates. Conclusion : Intervention efforts for this population are sorely needed and the information gained from this study can be used to guide these intervention efforts.